A COMMUNITY MENTAL HEALTH PROFESSIONAL DEVELOPMENT MODEL FOR THE EXPANSION OF REFLECTIVE PRACTICE AND SUPERVISION: EVALUATION OF A PILOT TRAINING SERIES FOR INFANT MENTAL HEALTH PROFESSIONALS. Issue 6 (2nd November 2016) - Shea, Sarah E.; Goldberg, Sheryl; Weatherston, Deborah J.
ABSTRACT: The Michigan Association for Infant Mental Health identified a need for reflective supervision training for infant mental health (IMH) specialists providing home‐based services to highly vulnerable infants and their families. Findings indicate that this pilot of an IMH community mental health professional development model was successful, as measured by the participants' increased capacity to apply reflective practice and supervisory knowledge and skills. Furthermore, IMH clinicians demonstrated an increase in the frequency of their use of reflective practice skills, and their supervisors demonstrated an increase in their sense of self‐efficacy regarding reflective supervisory tasks. Finally, the evaluation included a successful pilot of new measures designed to measure reflective practice, contributing to the growing body of research in the area of reflective supervision.